Prevalence of Hepatitis B and Hepatitis C Viruses in ? – thalassemias major patient in AD-Diwanya privince ,iraq (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: transmition of infectious agent is still the most common cause of death and disability related to blood transfusion. Objective: to estimate the prevalence of HBV and HCV in beta thalassemic major patients in Ad-Diwayah governorate. Method: The current study is a retrospective cross sectional study involving sample of 80 thalassemic major patients who regularly visit thalassemia center in Ad-diwuryah for treatment, data that required in the study had been collected from patients, their guardians and from the records. Results: The prevalence rate of HBV was 2.5% (l male and 1 Female ) which was significantly associated with family history of hepatitis ; while the prevalence rate of HCV was 3.8% (1male and 2 female) which was significantly associated with age and family history of hepatitis